Imagology as a Way to Recognize Mental Tools of Combat. With the Soviet Great Patriotic War (1941–1945) in the Background - Gliniecki, Tomasz (Tools of War, 2023)
Psychological and sociological tools of combat are much less well known and difficult to assess reliably, and they are not always assigned a meaning appropriate to the results achieved. The author of the article decided to bring closer experiences from the border of psychology, communication science and cultural studies, in order to present the impact of imagology, a science dealing with the ideas of some communities about others, on the war. A group waging a war deliberately influences the cognitive system of its members so that their ideas about the enemy gain a degree that allows them to effectively conduct the fight and, consequently, to win over him. On the way to the open conflict, and during its course, these images pass from a fairly neutral “image of the Other” to an extreme “enemy image”, intensifying the negative emotions towards the opponent. At the same time, in opposition, a “self-image” is built, justifying the need to fight and the positive qualities of one's own group. The Great Patriotic War of the Soviet Union with the Third German Reich was taken as an example here, showing the extreme hatred of both countries, manifested in the direct war clash of totalitarian regimes in 1941–1945. The main activity of Soviet propaganda at that time was to dehumanize the Germans as invaders and beasts who deserved only annihilation.